The green library initiative at Universiti Putra Malaysia - Kassim, Muzaffar Shah; Zainal Abidin, Azizah; Ab Rahman, Azwana; Sahak, Mohd Dasuki; Engku Mud, Tengku Nor Fazwani (Department of Library and Information Science, Faculty of Computer Science and Information Technology, University of Malaya and University of Malaya Library, 2019)
UPM Library is committed to play its significant role in supporting the mission of its parent institution to conserve the university environment through various eco-friendly, green activities and quality management systems based on sustainable and efficient environmental management. The case study is written based on experience of the library staff, who is involved in managing the green library initiative since June 2017 and the report that was submitted to the “Administration Management Star Rating Award 2018”. In this paper, the green libraries initiative around the world was briefly discussed and its implementation in UPM Library was described into five main elements such as budget, electricity saving, water saving, recycle paper and the initiative/ innovation implemented in the year 2018. In return, there are a lot of benefits after the implementation of the green initiative and UPM Library has shown green leadership capability among the UPM community which is reflected by winning one of the UPM awards that is second placing for the “Administration Management Star Rating Award 2018” during UPM Services Quality and Innovation Day. Green Sustainability is one of the components that were being evaluated for the purpose of this award.